Integrative multi-omics identifies AP-1 transcription factor as a targetable mediator of acquired osimertinib resistance in non-small cell lung cancer - Bengisu Dayanc; Sude Eris; Nazife Ege Gulfirat; Gulden Ozden-Yilmaz; Ece Cakiroglu; Ozlem Silan Coskun Deniz; Gökhan Karakülah; Serap Erkek-Ozhan; Serif Senturk (Cell Death and Disease)
Abstract Osimertinib, a third-generation EGFR tyrosine kinase inhibitor (EGFR-TKI), has dramatically transformed the treatment landscape for patients with EGFR-mutant NSCLC. However, the long-term success of this therapy is often compromised by the onset of acquired resistance, with non-genetic mechanisms increasingly recognized as pivotal contributors. Here, we exploit a multi-omics approach to profile genome-wide chromatin accessibility and transcriptional landscapes between drug sensitive and resistant EGFR-mutant cells. Our findings reveal a robust concordance between epigenetic regulome and transcriptomic changes that characterize the osimertinib resistant state. Through CRISPR-based functional genomics screen targeting epigenetic regulators and transcription factors, we uncover a critical regulatory network featuring key members of the NuRD and PRC2 complexes that mediate resistance. Most critically, our screen identifies FOSL1 and JUN, two subunits of the AP-1 transcription factor within this network, as the most significant hits. Mechanistically, we demonstrate that cis-regulatory elements exhibiting altered chromatin accessibility in the resistant state are enriched for cognate AP-1 binding motifs, enabling AP-1 to orchestrate a gene expression program that underpins the druggable MEK/ERK signaling axis, potentially enhancing cell viability and fitness of resistant cells. Importantly, genetic depletion or pharmacological inhibition of AP-1 reinstates cellular and molecular sensitivity, and reverts resistance-associated phenotypes, such as epithelial-to-mesenchymal transition, upon anti-EGFR rechallenge by repressing AKT and ERK signaling. These findings provide novel insights into the epigenetic and transcriptional control of osimertinib resistance in EGFR-mutant NSCLC, highlighting AP-1 as a targetable vulnerability of resistance-related hallmarks and offering a promising avenue for developing resistance reversal strategies.